2022
DOI: 10.3389/fphys.2022.892681
|View full text |Cite
|
Sign up to set email alerts
|

Eastward Jet Lag is Associated with Impaired Performance and Game Outcome in the National Basketball Association

Abstract: Objectives: Elite athletes are often required to travel across time zones for national and international competitions, causing frequent jet lag. The aim of this study was to examine whether the direction of travel-related jet lag is associated with performance in the National Basketball Association (NBA), and if so, to explore potential mechanisms.Methods: Ten seasons comprising of 11,481 games of NBA data from the 2011/2012 to the 2020/2021 regular season were analyzed using multi-level mixed models with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Therefore, if we cannot discern an effect of jet lag and game time on a large dataset of collegiate football games, it certainly calls into question previous studies suggesting these effects existed in NFL teams, 17,18 if not other professional sports. [14][15][16][17]19 Complex questions require complex models that do not have a "textbook" solution from which to draw inferences and conclusions. For many complex models, bootstrapping is a general solution from which one can derive standard errors and confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if we cannot discern an effect of jet lag and game time on a large dataset of collegiate football games, it certainly calls into question previous studies suggesting these effects existed in NFL teams, 17,18 if not other professional sports. [14][15][16][17]19 Complex questions require complex models that do not have a "textbook" solution from which to draw inferences and conclusions. For many complex models, bootstrapping is a general solution from which one can derive standard errors and confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In contrast to individual-level studies examining jet lag and human performance, 'big data' studies generally show an apparent effect of jet lag decreasing team performance. [14][15][16][17][18][19] However, all of these studies employ simplistic univariate analyses [16][17][18][19] and/or infer causality from simplistic multivariable correlations. 14,15,18,19 Such modeling is not strongly informed by theory (i.e., a putative causal structure) and may thus lead to fallacious causal inferences.…”
Section: Current Evidence On Jet Lag and Sport Performancementioning
confidence: 99%
“…However, not all the literature supports the notion that time zone change degrades competitive performance strictly in westward travel. Leota and colleagues (2022) evidenced that time zone change in the eastward, but not westward, direction was associated with reduced NBA winning percentage, as well as overall point, rebound, and field goal percentage differential [ 47 ]. Similarly, Zacharko and colleagues (2022) concluded that eastward travel across time zones associated with worse performance results than westward travel across time zones in a sample of professional soccer players [ 48 ].…”
Section: Sleep’s Role In Athletics At the Professional Levelmentioning
confidence: 99%
“…Beyond the aforementioned studies, we have also identified six other investigations that evaluated the effects of travel across time zones on competitive performance outcomes in professional athletes [44][45][46][47][48][49]. Since sleep health often degrades when traveling across time zones due to factors such as circadian disruption, travel fatigue, and irregular sleep behaviors [50], these findings in this section appear most appropriate for the review.…”
Section: Travel and Time Zone Change: Negative Influence On Sleep Tha...mentioning
confidence: 99%
“…Chronic stressors—both within and outside of their job—also impact performance and wellbeing. For example, frequent and long-distance air travel is known to disrupt sleep and circadian rhythms which can lead to chronic jet lag and impair performance ( Fowler et al, 2017 ; Leota et al, 2022 ). Similarly, after a long-term injury, athletes report mental health symptoms and a low level of psychological readiness to return to competition at their best despite full physical recovery ( Ruddock-Hudson et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%